2021
DOI: 10.1111/acel.13452
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic age prediction

Abstract: Advanced age is the main common risk factor for cancer, cardiovascular disease and neurodegeneration. Yet, more is known about the molecular basis of any of these groups of diseases than the changes that accompany ageing itself. Progress in molecular ageing research was slow because the tools predicting whether someone aged slowly or fast (biological age) were unreliable. To understand ageing as a risk factor for disease and to develop interventions, the molecular ageing field needed a quantitative measure; a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 208 publications
(369 reference statements)
4
100
0
Order By: Relevance
“…Several mammalian epigenetic aging clocks have been developed with the aim of expediting the discovery and validation of therapeutics and interventions to attenuate, prevent, or reverse biological aging (Simpson & Chandra, 2021 ). Zymo Research's validated DNAge™ algorithm, which expands upon the Horvath pan‐tissue clock built using elastic net regression (Horvath, 2013 ) and is accurate in murine muscle, was used to compare the chronological age of muscle from aged sedentary and PoWeR animals to that of young animals.…”
Section: Resultsmentioning
confidence: 99%
“…Several mammalian epigenetic aging clocks have been developed with the aim of expediting the discovery and validation of therapeutics and interventions to attenuate, prevent, or reverse biological aging (Simpson & Chandra, 2021 ). Zymo Research's validated DNAge™ algorithm, which expands upon the Horvath pan‐tissue clock built using elastic net regression (Horvath, 2013 ) and is accurate in murine muscle, was used to compare the chronological age of muscle from aged sedentary and PoWeR animals to that of young animals.…”
Section: Resultsmentioning
confidence: 99%
“…Differences between GSEA results of different outcome variable types could also arise from different biological information captured by the metabolic surrogates and by reported or measured values. This phenomenon is known from epigenetic clocks whose age predictions can differ from chronological age, and different clocks can reflect different aspects of biological age [38]). While many of the top-ranked pathways (S1 Appendix) for smoking were found by both outcome variable types, some of the pathways were solely found by using either reported smoking status ("smoking current") or metabolic surrogate("s current smoking").…”
Section: Discussionmentioning
confidence: 99%
“…As a key component of post-transcriptional modification, DNA methylation has been intensively reported to be involved in the regulation of cancer-associated genes [ 36 , 37 ]. In our study, we found that the methylation level of all the GSDMs members is significantly reduced in HCC tissues, which puts us in mind of the increased expression of GSDMs in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%